Ibtikāru taqwīmi al-mahārāti al-istiqbāliyyati fī al-lughati al-‘Arabiyyati al-qāʾimi ‘alā manṣati Kuīzīz (Quizizz) fī kitābi al-lughati al-‘Arabiyyati liṣ-ṣaffi ath-thālithi (KMA 2020) - Hikmal Akbar; Ahmad Riyadissolihin; R. Umi Baroroh; Fatin Natasya Binti Hasan Ashari (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study aims to develop an assessment instrument for Arabic receptive skills based on the Quizizz platform for third-grade students at Islamic elementary schools (madrasah ibtidaiyah) in accordance with KMA 2020. The method employed is Research and Development (R&D) using the ADDIE model, implemented up to the development stage. The development process began with a needs analysis of the curriculum, student characteristics, and current assessment practices, followed by the design of item grids and the development of 48 test items comprising 20 audio-based listening items and 28 reading items supported by texts and images. Validation was conducted by three validators consisting of a content expert, an evaluation expert, and a media expert. The validation results yielded an average score of 88.55%, classified as highly feasible. The instrument integrates multimedia and gamification features of Quizizz, including audio, visual illustrations, a point system, leaderboard, timer, and automatic feedback, making the assessment more interactive, engaging, and efficient. In conclusion, the Quizizz-based assessment instrument meets the criteria of content validity, construct validity, and media feasibility, making it a viable alternative for Arabic language learning assessment in the digital era.